The Edinburgh companion to contemporary liberalism - Evans, Mark, 1965 September 27- (Edinburgh University Press, 2001)
This is the premier collection of material on a comprehensive range of topics in contemporary liberalism. It shows how liberalism can tackle wide-ranging practical concerns that urgently demand attention in twenty-first century politics.